Application of the idealized structural unit method for ultimate strength analyses of stiffened plate structures. Issue 1 (2nd January 2017) - Lindemann, Thomas; Kaeding, Patrick
ABSTRACT: To assess the safety of ship structures, the determination of the ultimate hull girder strength is of essential importance. The idealized structural unit method (ISUM) is a simplified method to perform progressive collapse analyses of large structural systems with less computational efforts compared to non-linear finite element analyses (FEA). In this paper, the basic concept and the applicability of ISUM are demonstrated for a stiffened plate panel under lateral pressure and inplane thrust. Ship structures are subjected to global bending moments and lateral pressure loads. To simulate the collapse behaviour of such complex structural systems, a box-girder specimen in bending is investigated. Appropriate numerical models are presented and the corresponding ultimate strength values are validated against experimental results. To simulate combined load cases with lateral pressure loads acting on the bottom of the box-girder specimen, the corresponding ultimate strength values determined with ISUM are compared with non-linear FEA results.